Joining suitability of cast aluminium for self-piercing riveting. Issue 1 (June 2021) - Neuser, M; Kappe, F; Busch, M; Grydin, O; Bobbert, M; Schaper, M; Meschut, G; Hausotte, T
Abstract: Due to the increasing importance of reducing CO2 emissions, lightweight construction strategies are highly emphasized in the automotive industry. One of these strategies is lightweight moulding, which is used, for example, in the space frame design. Here, lightweight materials are joined with castings to form a structure that is well adapted to the application of force. Especially for multi-material joints, self-piercing riveting is frequently used as joining technology due to the wide range of joining possibilities and the high load-bearing capacities. However, the susceptibility of cast aluminium alloys to cracking due to the brittle microstructure causes great challenges for mechanical joining by self-piercing riveting. Therefore, this study investigates the suitability of the cast aluminium alloy AlSi9Mn for self-piercing riveting. Various improvement strategies are utilized to increase suitability considering of joining as well as material parameters. An evaluation of the joint and its damage characteristics is provided by metallographic analysis and industrial X-ray computed tomography (XCT). Metallographic analysis is used to determine the quality relevant characteristics of the joint, while XCT provides volumetric and non-destructive testing of the joint for internal cracks.